2007
DOI: 10.1242/jcs.011213
|View full text |Cite
|
Sign up to set email alerts
|

Dictyostelium Hip1r contributes to spore shape and requires epsin for phosphorylation and localization

Abstract: Clathrin-coated pits assemble on the plasma membrane to select and sequester proteins within coated vesicles for delivery to intracellular compartments. Although a host of clathrin-associated proteins have been identified, much less is known regarding the interactions between clathrin-associated proteins or how individual proteins influence the function of other proteins. In this study, we present evidence of a functional relationship between two clathrin-associated proteins in Dictyostelium, Hip1r and epsin. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 70 publications
(86 reference statements)
4
23
0
Order By: Relevance
“…2D,F). This round spore phenotype was reminiscent of Dictyostelium Hip1r, another clathrin accessory protein (Repass et al, 2007). The restricted phenotype during development supported an essential role for epsin in a specialized pathway that controls the correct morphology of spores.…”
Section: Epsin-null Mutants Display Limited Clathrin-associated Phenomentioning
confidence: 83%
See 1 more Smart Citation
“…2D,F). This round spore phenotype was reminiscent of Dictyostelium Hip1r, another clathrin accessory protein (Repass et al, 2007). The restricted phenotype during development supported an essential role for epsin in a specialized pathway that controls the correct morphology of spores.…”
Section: Epsin-null Mutants Display Limited Clathrin-associated Phenomentioning
confidence: 83%
“…At present, little is known about how Dictyostelium spores construct their oblong shape. Interestingly, the clathrin accessory protein Hip1r also forms abnormally round spores in Dictyostelium (Repass et al, 2007). Both epsin-null cells and Hip1r-null cells produce round spores with slightly reduced viability, but Hip1r-null spores are more sensitive to heat and detergent treatment, indicating that the spore phenotype of Hip1r-null cells is more severe (Repass et al, 2007).…”
Section: Determinants Within the Enth Domain That Contribute To Epsinmentioning
confidence: 99%
“…Interestingly, in Dictyostelium discoideum plasma membrane localization of the Sla2 homolog Hip1r depends on epsin's ENTH domain (36). This dependence strongly suggests that the interaction between the lipid-binding domains of these two proteins is highly conserved.…”
Section: Sla2∆thatch-acb-gfp Ent1∆acbmentioning
confidence: 99%
“…Evidence for CME in Dictyostelium is based on the observation that clathrin forms plasma membrane puncta that colocalize with AP2, epsin, Hip1r and AP180 (Stavrou and O'Halloran, 2006;Repass et al, 2007;Brady et al, 2008;Wen et al, 2009;Sosa et al, 2012). In the case of AP2, immunofluorescence studies using an antibody to the a or b1/2 subunits showed that they localize to clathrin puncta (Wen et al, 2009;Sosa et al, 2012).…”
Section: Introductionmentioning
confidence: 99%